Spiritual Immersion: Developing and Evaluating a Simulation Exercise to Teach Spiritual Care to Undergraduate Nursing Students. Issue 4 (July 2017) - Galloway, Sharon; Hand, Mikel W.
Abstract : This article describes the development, implementation, and evaluation of a simulation exercise designed to teach spiritual care to prelicensure nursing students. Participation in a spiritual care simulation resulted in improved knowledge and attitudes relating to spirituality and spiritual care. The results from this study demonstrate the value of using simulation and spiritual assessment to teach students how to recognize and respond therapeutically to spiritual needs.